Making administration responsive in grievances hearing: A new technique (Note) - Selvaraj, B.V. (1997)
The author discusses inadequacies of the existing Government-Public interface and spells out what minimum needs to be done to improve the existing grievance-redressal arrangement. He then introduces a new technique devised by him, based on a `Grievances Hearing Sheet', adoption of which, according to him, would make administration "truly responsive" in this regard. - Reproduced
Keywords: Note; Public administration